2017
DOI: 10.1002/2211-5463.12320
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoding thioacetyl‐lysine as a non‐deacetylatable analog of lysine acetylation in Escherichia coli

Abstract: Reversible lysine acetylation is one of the most widely distributed post‐translational modifications; it is involved in a variety of biological processes and can be found in all three domains of life. Acetyltransferases and deacetylases work coordinately to control levels of protein acetylation. In this work, we applied the genetic code expansion strategy to site‐specifically incorporate Nε‐thioacetyl‐l‐lysine (TAcK) as an analog of Nε‐acetyl‐l‐lysine (AcK) into green fluorescent protein and malate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 64 publications
(72 reference statements)
2
27
0
Order By: Relevance
“…We showed that TAcK residues could be recognized by the AcK antibody and the effect of thioacetylation was similar to that of acetylation on the enzyme activities of malate dehydrogenase, indicating that TAcK could be an ideal mimic of AcK in acetylation studies. Furthermore, we confirmed that TAcK residues could resist the deacetylase [ 45 ]. This system will be particularly useful if long-lasting effects of acetylation need to be determined in living cells with the concern of endogenous deacetylases.…”
Section: Lysine Acetylation and Its Analogs By Genetic Code Expanssupporting
confidence: 62%
See 1 more Smart Citation
“…We showed that TAcK residues could be recognized by the AcK antibody and the effect of thioacetylation was similar to that of acetylation on the enzyme activities of malate dehydrogenase, indicating that TAcK could be an ideal mimic of AcK in acetylation studies. Furthermore, we confirmed that TAcK residues could resist the deacetylase [ 45 ]. This system will be particularly useful if long-lasting effects of acetylation need to be determined in living cells with the concern of endogenous deacetylases.…”
Section: Lysine Acetylation and Its Analogs By Genetic Code Expanssupporting
confidence: 62%
“…Later, by flexizyme-mediated tRNA aminoacylation, Xiong et al were able to incorporate thio-acetyllysine (TAcK) into histone H3 site-specifically with the cell-free translation system [ 44 ]. Recently, our group further engineered the AcKRS for recognition of TAcK and successfully incorporated TAcK into proteins in E. coli cells [ 45 ]. We showed that TAcK residues could be recognized by the AcK antibody and the effect of thioacetylation was similar to that of acetylation on the enzyme activities of malate dehydrogenase, indicating that TAcK could be an ideal mimic of AcK in acetylation studies.…”
Section: Lysine Acetylation and Its Analogs By Genetic Code Expansmentioning
confidence: 99%
“…So, those proteins may not reach 100% acetylation at specific sites. Recently, we have established a thio-acetyllysine incorporation system which can be used as a non-deacetylable analog of acetyllysine 43 , thus this system could be a good alternative approach in this case.…”
Section: Discussionmentioning
confidence: 99%
“…X is the growth rate in the exponential phase, which was automatically provided by Gen5 software designed for the BioTek microplate reader (Winooski, VT, USA). The monitoring of GFP expression by fluorescence followed previous studies [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%